Efektivitas Komunikasi Visual Melalui Prinsip-Prinsip User Experience Design (UXD) Pada Website Virtual Event Festival Sains dan Budaya - Abdul Kholik; Asep Soegiarto; Wina Puspita Sari (Jurnal ilmiah Sistem Informasi dan Ilmu Komputer, 2024)
This study aims to analyze the effectiveness of visual communication through the application of User Experience Design (UXD) principles on the virtual event website of Festival Sains dan Budaya. In the context of virtual events, effective visual communication plays a pivotal role in attracting user participation, conveying information clearly, and ensuring a positive user experience. The research employs a qualitative method, incorporating interviews, observations, and focus group discussions (FGDs) involving virtual event organizers, graphic designers, and website developers. The collected data were analyzed using content analysis to identify the implementation of UXD principles on the website festivalsainsbudaya.com/virtual-2024. The findings reveal four main categories of UXD implementation. First, Scale for Layout Setting, which includes minimalist header and footer design, centralized alignment, enlarged link access, and the use of wide whitespace to enhance readability. Second, Visual Hierarchy as Site Mapping/Intuitive, emphasizing a striking first impression and clear menu options presented at the start for intuitive navigation. Third, Balance & Contrast at the Same Time, achieved through contrasting button links, consistent design patterns, and the application of a global template to maintain brand coherence. Fourth, Media Interactive and Entertain Primarily, featuring feedback forms, varied media formats, high readability, motion elements, and easy navigation to increase user engagement. Overall, the virtual event website demonstrates strong adherence to UXD principles, resulting in intuitive navigation, a clear and logical information hierarchy, consistent visual design, and interactive media integration that enhances user engagement. These findings indicate that the application of UXD principles not only supports effective visual communication but also contributes significantly to user satisfaction and participation rates. This research underscores the importance of aligning UXD strategies with the goals of virtual cultural events, offering practical insights for future website development in the fields of culture, science, and public engagement.